2022
DOI: 10.1039/d2ra02030k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of gas molecules on buckled GaAs monolayer: a first-principles study

Abstract: NH3, NO2, and SO2 chemisorb on the GaAs monolayer. NO adsorption induces a magnetic moment (1.02 μB per cell), and significantly changes the conductivity and reflectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…28 The pristine B 3 O 3 monolayer has been reported for dual application in sensing COVID-19 biomarkers as well as drug delivery for treating the disease. 29 III-As monolayers such as BAs 30 and GaAs 31 have shown potential for gas sensing applications as reported previously. The thermal and electrical conductivity of the BA monolayer can be altered using electrical and external magnetic fields.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…28 The pristine B 3 O 3 monolayer has been reported for dual application in sensing COVID-19 biomarkers as well as drug delivery for treating the disease. 29 III-As monolayers such as BAs 30 and GaAs 31 have shown potential for gas sensing applications as reported previously. The thermal and electrical conductivity of the BA monolayer can be altered using electrical and external magnetic fields.…”
Section: Introductionsupporting
confidence: 53%
“…Past studies have demonstrated that this sensitivity can surpass 100% and may even extend to a substantial order of 10. 31,58 For acetone and butanone, GaAs has significantly high sensitivity. The BAs monolayer displays insignificant sensitivity in this case too.…”
Section: E Voc Sensing Performance Of the Iii-as Monolayermentioning
confidence: 99%
“…The ϕ value before and after the Cc adsorption is given in Figure a. The work function sensitivity or surface sensitivity can be calculated by the following equation , S ϕ = normalΔ ϕ ϕ h o s t × 100 % …”
Section: Results and Discussionmentioning
confidence: 99%
“…The ϕ value before and after the Cc adsorption is given in Figure 12a. The work function sensitivity or surface sensitivity can be calculated by the following equation 56,57 = × S 100% host (11) The Δϕ values for p-2DPA and Pd-2DPA after the Cc adsorption are 0.13 and 0.37 eV, respectively. Therefore, the S ϕ values for p-2DPA and Pd-2DPA are 2.05 and 6.35%, respectively, implying that Pd-2DPA is more sensitive toward the Cc molecule than p-2DPA.…”
Section: Recovery Timementioning
confidence: 99%
“…Ga 12 As 12 has been investigated for a variety of applications. Shahriar et al reported the adsorption of 10 gases on the monolayer Ga 12 As 12 surface and confirmed the surface sensitivity and response to the adsorbed gases . Rouzhahong and co-workers studied the photocatalytic activity of the GaAs monolayer.…”
Section: Introductionmentioning
confidence: 85%